An economic model to estimate the relative costs over 20 years of different hip prostheses. Issue 9 (1st September 1999) - Baxter, K; Bevan, G
Abstract : STUDY OBJECTIVE: To determine the relative costs of prostheses and factors associated with changes in these cost rankings. DESIGN AND SETTING: Economic model using published data. MAIN RESULTS: The main cost drivers are current costs and revision rates. Expected revision costs are a small proportion of the expected total costs. There are few competitors to the "gold standard" Charnley in terms of total expected costs over 20 years. There is no monetary advantage in using higher cost prostheses in older patients even if they were to have lower revision rates. There may be a monetary case for using prostheses with higher costs and lower revision rates in younger patients. CONCLUSIONS: The most cost effective prosthesis in older patients is the Stanmore. The Charnley, Exeter Polished and Muller Straight Stem are marginally more costly than the Stanmore. The study inevitably lacks good data on survival for newer prostheses. This does not affect the ability to make choices for older patients. Data are needed, however, on survival of cemented prostheses for younger patients.